Hungarian Monitoring, 29 August 1988 . [Magyar rádiófigyelő], 1988. augusztus 29 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Knowledge of history in the USSR - Czechoslovak foreign minister in Bonn talks - Polish situation Domestic Affairs: - Summary of Ceauşescu-Grósz meeting - Reactions to the meeting in socialist countries and the West - Church leaders swear oath to Hungarian constitution - "Liget" periodical to appear within days Economy: - Awkwardness of personal income tax Külpolitika: - Történelemtudat a Szovjetunióban - Bonnban tárgyal a csehszlovák külügyminiszter - A lengyel helyzet Belpolitika: - Összefoglaló a Ceauşescu-Grósz találkozóról - A találkozó visszhangja a szocialista országokban és a nyugati világban - Egyházi vezetők tesznek esküt a magyar alkotmányra - A napokban jelenik meg a Liget folyóirat Gazdaság: - A személyi jövedelemadó visszásságai